Roles for the Rhodobacter sphaeroides CcmA and CcmG Proteins - Cox, Rebecca L. (American Society for Microbiology, 2001)
Rhodobacter sphaeroides cells containing an in-frame deletion within ccmA lack detectable soluble and membrane-bound c-type cytochromes and are unable to grow under conditions where these proteins are required. Only strains merodiploid for ccmABCDG were found after attempting to generate cells containing either a ccmG null mutation or a ccmA allele that should be polar on to expression of ccmBCDG, suggesting that CcmG has another important role in R. sphaeroides.